Ripensando l’equazione di reazione - Tifi, Alfredo (Chimica nella Scuola, 2024)
The Project ASSeT, currently underway at ITTS Divini in San Severino Marche, focuses on strengthening the basic tools for the mathematization of reality, both in its quantitative and qualitative aspects. Considering previous activities on stoichiometric relationships, we recognized the need to modify the symbolic description to bring it closer to the essential and systemic aspects of the particle model of chemical reactions. We consider the iconic register presented in the article suitable for this purpose and believe it should be practiced before introducing the typical formalism of chemical equations.